2016
DOI: 10.1128/aac.02830-15
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of the Effect of Inflammation on Voriconazole Trough Concentrations

Abstract: f Voriconazole (VCZ) exhibits great inter-and intrapatient variability. The latter variation cannot exclusively be explained by concomitant medications, liver disease or dysfunction, and genetic polymorphisms in cytochrome P450 2C19 (CYP2C19). We hypothesized that inflammatory response in patients under VCZ medication might also influence this fluctuation in concentrations. In this study, we explored the association between inflammation, reflected by the C-reactive protein (CRP) concentration, and VCZ trough c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 34 publications
3
40
1
Order By: Relevance
“…Nevertheless, we need further studies investigating the effect of corticosteroid dosing on voriconazole metabolism as well as the effect of different glucocorticoids. In addition, the effect on voriconazole concentration caused by prednisone in the present case was higher to the observed in previous studies (a 5.60‐fold increase in voriconazole concentration when prednisone was discontinued); therefore, other causes may have contributed to decrease the elimination of the drug from the blood such as the inflammatory state of the patient .…”
Section: Dips Algorithm (Drug Interaction Probability Scale); the Intcontrasting
confidence: 83%
“…Nevertheless, we need further studies investigating the effect of corticosteroid dosing on voriconazole metabolism as well as the effect of different glucocorticoids. In addition, the effect on voriconazole concentration caused by prednisone in the present case was higher to the observed in previous studies (a 5.60‐fold increase in voriconazole concentration when prednisone was discontinued); therefore, other causes may have contributed to decrease the elimination of the drug from the blood such as the inflammatory state of the patient .…”
Section: Dips Algorithm (Drug Interaction Probability Scale); the Intcontrasting
confidence: 83%
“…The possible relationship between upregulation of VCZ and specific proinflammatory markers had not yet been described. Recently, a study with a comparable design and patient group was published, using another linear mixed model to determine the association of CRP with VCZ concentrations . We used a different type of linear mixed model because of the skewness of our data, which made log‐transformation essential.…”
Section: Discussionmentioning
confidence: 99%
“…The Gaussian serial covariance structure in combination with a random intercept takes into account the fact that observations within a patient decrease if the time between observations increases. This resulted in lower values of AIC compared with using other approaches . The lower values of the AIC indicate a better fit of our data in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in adults, it was shown that severe inflammation, reflected by C‐reactive protein (CRP) value, was associated with elevated voriconazole trough concentrations . This was explained by inflammatory stimuli leading to downregulation of CYP isoenzymes, resulting in reduced metabolism of voriconazole .…”
Section: Table Of Linksmentioning
confidence: 99%